Analysis of Social Wellbeing Parameters in Russia; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Maklakova T. G. Taisiya Glebovna; Bulatova T. A.; Berestneva O. G. Olga Grigorievna; Romanchukov S. V.; Shukharev S. O. (2017, 2017)
Title screen